The artistic practice of Regina José Galindo: Anatomy of an emancipatory metaphor - Martín Vodopivec, Yasmin (2019)
Through history, the relationship of poetry with other fine arts has been an object of numerous studies based mainly in comparative criteria. The poetic language transcends the boundaries of literature and turns into a key element to determine if the work is work of art. The form, the perception and the execution of the performance which in its origins was linked to the representative act based on the text as an artistic form of expression, in the latinamerican context is transformed into a protest element in the social mobilizations related to the human rights’ defense. The main exponent of performance art in Guatemala, Regina José Galindo (born in 1974), started her career in the field of poetry. Her performances establish formal and functional connections with the poetic language, creating metaphors through the subject, the object and the action, that are used as a catalyzer of the message to be transmitted and create another type of reception, that goes beyond the everyday limits that circumscribe both disciplines. The performance metaphors of the artist, besides questioning the social position of women, accomplish the observer to reach through identification, the emancipatory experience in its whole.